2015
DOI: 10.1371/journal.pntd.0003583
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Increased Dose and Frequency of Albendazole with Standard Dose DEC for Treatment of Wuchereria bancrofti Microfilaremics in Odisha, India

Abstract: Although current programmes to eliminate lymphatic filariasis have made significant progress it may be necessary to use different approaches to achieve the global goal, especially where compliance has been poor and ‘hot spots’ of continued infection exist. In the absence of alternative drugs, the use of higher or more frequent dosing with the existing drugs needs to be explored. We examined the effect of higher and/or more frequent dosing with albendazole with a fixed 300mg dose of diethylcarbamazine in a Wuch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…No trials included in the review assessed treatment twice per year with albendazole, so we could not determine whether the WHO recommendation for albendazole alone twice per year to treat lymphatic filariasis in loiasis‐endemic areas is supported ( WHO 2012 ). Other studies have reported a benefit of an increased dose or frequency of albendazole for individual treatment and community control, but these were either not placebo‐controlled trials ( Pion 2015 ), or were not designed to assess the effects of albendazole alone ( Kar 2015 ; Tafatatha 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No trials included in the review assessed treatment twice per year with albendazole, so we could not determine whether the WHO recommendation for albendazole alone twice per year to treat lymphatic filariasis in loiasis‐endemic areas is supported ( WHO 2012 ). Other studies have reported a benefit of an increased dose or frequency of albendazole for individual treatment and community control, but these were either not placebo‐controlled trials ( Pion 2015 ), or were not designed to assess the effects of albendazole alone ( Kar 2015 ; Tafatatha 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This trial did not compare albendazole co‐administered with ivermectin to ivermectin for lymphatic filariasis Dembele 2010 The comparison groups – albendazole plus ivermectin given together at increased dose and frequency versus the standard dose of albendazole plus ivermectin – do not provide answers to question of whether adding albendazole to ivermectin improves treatment outcomes Ismail 1998 The comparison groups – albendazole versus albendazole plus ivermectin versus albendazole plus DEC versus DEC plus ivermectin – do not match those in the review; these comparisons do not provide answers to the question of whether adding albendazole to ivermectin or DEC improves outcomes compared to ivermectin or DEC alone Jayakody 1993 The comparison groups ‐ albendazole versus DEC ‐ did not match those in the review; this does not provide answers to the question as to whether adding albendazole to DEC improves outcomes compared to DEC alone. Kar 2015 The comparison groups – albendazole plus DEC given together at increased dose and frequency versus the standard dose of albendazole plus DEC – do not provide answers to the question of whether adding albendazole to DEC improves treatment outcomes King 2018 The comparison groups – albendazole plus DEC given annually versus albendazole plus DEC given once versus albendazole plus DEC plus ivermectin given once – do not provide answers to the question of whether adding albendazole to DEC improves treatment outcomes Makunde 2003 Comparison groups do not match those in review; for single infections with W bancrofti these were albendazole plus ivermectin versus albendazole alone; for co‐infections of W bancrofti and Onchocerca volvulus these were ivermectin plus albendazole versus placebo Namwanje 2011 The comparison groups for people with lymphatic filariasis – albendazole plus ivermectin plus praziquantel versus albendazole plus ivermectin with no praziquantel or praziquantel given after 1 week – do not match those of the review; this does not provide answers to the question of whether adding albendazole to ivermectin improves treatment outcomes Nash 2017 Although the comparison groups ‐ albendazole versus placebo ‐ match those sought by the review, the study did not include the patient population relevant to the review (participants were not infected by W bancrofti ) Pion 2015 Not an RCT; all individuals were given albendazole in a community study Shenoy 1999 The comparison groups – albendazole versus albendazole plus ivermectin versus albendazole plus DEC versus DEC plus ivermectin – do not match those in the review. …”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of filariasis cases during 2016-18 continued to decline in line with the implementation of filariasis MDA carried out in those years. The drugs used were a combination of Diethyl Carbamazine Citrate (DEC) and Albendazole, which have been shown to be effective in decreasing the density of microfilariae (Kar et al, 2015). The results of mass treatment evaluation in Alor Island also showed that the use of Diethyl Carbamazine Citrate (DEC) and…”
Section: Filariasis Cases Distributions Based On People Time and Placementioning
confidence: 99%
“…In conclusion, the following strategy may be adapted for successful elimination of LF in Assam: ( i ) Instead of district as implementation unit, PHCs may be regarded as implementation unit for LF elimination; ( ii ) Involvement of tea estate owners and worker community in the MDA programme; ( iii ) Programme managers must ensure covering of all tea garden worker population under MDA irrespective to the endemicity status of the PHC; and ( iv ) Biannual dose of MDA with DEC and albendazole may be adapted as it has shown better compliance and will also reduce the span of MDA 29 .…”
mentioning
confidence: 99%